Macular perfusion, thickness, and sensitivity in phacovitrectomy versus lens-sparing vitrectomy in rhegmatogenous retinal detachment - Ahmed A Abdel Kader; Mina Abdelmalak; Ayman G Elnahry; Dalia A Ghalwash; Soheir Esmat; Asmaa Shuaib (Delta Journal of Ophthalmology)
Purpose The aim of this study was to compare phacovitrectomy (phacoPPV) to lens-sparing pars plana vitrectomy (PPV) with respect to macular perfusion, thickness, and sensitivity in phakic patients with rhegmatogenous retinal detachment.